Intergovernmental Impact Analysis in Optimizing the Implementation of the Village Profile and Administration Management Information System in Merjoyo Village, Purwoasri District, Kediri Regency - Ardiansyah, Yudha; Eprilianto, Deby Febriyan (Journal of Governance and Public Affairs, 2024)
The Government of Kediri District through the Office of Community Empowerment and Village Administration created the Village Profile and Administration Management Information System (SIMPADE). The existence of the SIMPADE application is expected to help the performance of the village government in the service of making population certificates. This research is a descriptive research with a qualitative approach. The focus of this research is to determine the impact of the application of SIMPADE as a form of village cooperation with the implementing elements of village government affairs in Merjoyo Village, Purwoasri District, Kediri Regency. Data collection techniques through semi-structured interviews, direct observation, and documentation review. Data analysis techniques consist of data reduction, data presentation and conclusion drawing. The results of this study indicate that the impact of the SIMPADE application on the provision and dissemination of service information is quite good because it provides options and has the potential for further development even though there are some obstacles regarding the operation of the application in the field.